The Snakes and Ladder on Speaking Ability in Children 5-6 Years - Ratnadi, Ni Nyoman Ari; Marleni, Kadek Devy; Arlinayanti, Kadek Dwi (JL3T (Journal of Linguistics, Literature and Language Teaching), 2021)
Early childhood is also called the golden age because children's physical and motor skills develop and grow rapidly, both in terms of emotional, intellectual, and moral development. The development of cognitive abilities is the development of basic skills to improve children's abilities, one of which is the ability to speak, especially the ability to speak English which is a development to become a bilingual school. Snakes and ladders is a game that is used as a game medium to improve cognitive development (speaking) in children where this game contains pictures of snakes and ladders as well as instructions in English that must be done which are divided into small boxes to connect one box to another. This study aimed to analyze the effect of Snakes and Ladders Game on English Speaking Ability in Children 5-6 Years at TK Negeri Pembina, Banjar District. This study used a pre-experimental design with a one-group pre-post test design, the sample size in this study was 38 respondents who were taken by using purposive sampling technique. This study used the Paired-t-test, the p value (0.00) < (0.05), it means that H0 was rejected and Ha was accepted. It concluded that there is an effect of Snakes and Ladders Game on English Speaking Ability in Children 5-6 Years at TK Negeri Pembina, Banjar District.